Group policy : fundamentals, security, and the managed desktop - Moskowitz, Jeremy (Indianapolis, Ind. : Wiley, 2010)
"The ultimate Group Policy guide-now updated for Windows 7 and Server 2008 R2! IT and network administrators can streamline their Windows Server management tasks by using Group Policy tools to automate or implement rules, processes, or new security across the enterprise. In this comprehensive guide, Microsoft Group Policy MVP Jeremy Moskowitz thoroughly explores Group Policy across all Windows platforms, including the latest on Windows 7 and Server 2008 R2. If you're a Windows network administrator managing scores of users and computers, you need this essential reference on your desk. Covers the fundamentals and beyond of Group Policy, a collection of tools and settings that allow administrators to manage users and computers across a Windows Server enterprise. Reflects the very latest Windows Server technologies: Windows Server 2008 R2 and Windows 7. Includes essential topics such as Group Policy settings, using the management console, implementing security, maintaining settings as users move from one computer to another, using Windows Steady State, and more. Offers expert guidance and advice from renowned Group Policy expert and Microsoft Group Policy MVP Jeremy Moskowitz. If you're a Windows Server network or IT administrator, make your life easier with Group Policy and this must-have guide"--
Includes index.
Keywords: Microsoft Windows (Computer file); Operating systems (Computers); Software configuration management; Computer security; Directory services (Computer network technology)